Teacher's Strategy in Fostering Students Empathy through Thematic Learning Approach in Elementary School - Manda, Darman; Arifin, Iqbal (Universitas Sulawesi Barat, 2024)
Empathy is an essential social skill in child development, especially in primary school. Developing empathy in children helps them manage better social relationships and builds a caring character towards others. While the main focus in primary education often lies on academic achievement, social-emotional development, including empathy, should receive more attention. Thematic learning integrates various subjects in one theme relevant to students' real lives and offers an effective approach to fostering empathy. This article uses the literature review to analyze relevant sources on strategies to develop empathy through thematic learning in primary schools. The researcher reviewed scientific articles, books, and journals that discuss the implementation of thematic learning, character development, and empathy in primary education. Based on this literature review, thematic learning can create space for students to understand and feel the feelings of others through collaboration, social interaction, and character values-based learning. This research also shows the importance of the teacher's role in designing and implementing thematic learning that involves social values, including empathy. Thus, thematic learning can improve students' academic achievement and develop the social-emotional skills needed to form a more harmonious and tolerant society.